Rancangan Strategi Pemasaran Digital Terintegrasi Pada Produk Kopi Palasari Menggunakan Metode SOSTAC - Gabero, Sandy; Yudha, Eka Purna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Girisenang Cooperative is one of the coffee producers in Bandung Regency, West Java. The cooperative sells coffee products in the form of green beans and roasted beans (Kopi Palasari). In 2023, the average monthly sales of Kopi Palasari were 350 kg, while Girisenang Cooperative has the capacity to produce 1000–1500 kg of roasted beans per month. The low sales of Kopi Palasari are attributed to suboptimal marketing activities, particularly digital marketing. This study aims to design an integrated digital marketing strategy for Kopi Palasari using the SOSTAC method, which consists of six stages: situation analysis, objectives, strategy, tactics, action, and control. The study identified the target market for Kopi Palasari as coffee enthusiasts, coffee shops, and Generation X to Generation Z consumers. Kopi Palasari will be positioned as a masstige brand, providing a luxurious and exclusive impression at an affordable price. Based on the situation analysis, Kopi Palasari will adopt a primary strategy of optimizing social media through content marketing and influencer marketing tactics. The optimization of social media aims to increase public awareness of the Kopi Palasari brand. Additionally, Customer Relationship Management (CRM) will be implemented in all consumer interactions with Kopi Palasari's social media and e-commerce platforms.